Influence Of Capital Funds, Infrastructure Means, And Professionalism Human Resources On Service Quality And Patient Satisfaction Of Puskesmas District Polewali Mandar West Sulawesi - Patandianan, Sriharni; Ratnawati, Tri; Sardjono, Sigit (Archives of Business Research, 2018)
Social security is a Universal Declaration of Human Rights as well as nationally (the 1945 Constitution and various other laws and regulations). The problems that often arise in relation to the BPJS tariff that has been determined in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 69 Year 2013 on the Health Service Tariff Standard At First Level Health Facilities And Health Facilities Continued Level In The Implementation Of Health Insurance Program. The fulfillment of access to health services, then the community of JKN users began to pay attention to the quality of service shown by their satisfaction to receive services from BPJS Health faskes. Based on the results of interviews with BPJS Health Branch Office of Polewali Mandar district obtained data regarding the complaints of JKN participants in FKTP in Polewali Mandar District include less friendly service, less informative, long queues, rejection of patients outside the region and unserved patients for medical treatment outside FKTP working hours. This is an indication of problems in patient satisfaction JKN while patient satisfaction is one of the target in the implementation of JKN program. This study aims to analyze the effect of Capitation Fund on service quality, analyze the effect of Kapuas Fund on patient satisfaction, analyze the effect of infrastructure facilities on service quality, analyze the influence of infrastructure facilities on patient satisfaction, analyze the influence of professionalism HR on service quality, analyze the influence of professionalism HR toward satisfaction patients, and analyzed the effect of service quality on patient satisfaction of Puskesmas in Polewali Mandar regency of West Sulawesi.